THE DEVELOPMENT OF ORGANIC FARMING IN VIETNAM - Mayasuri Presilla (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2018)
Organic products nowadays are very potential to be developed because of the increasing demand from consumers around the world on safe food which are free from agrochemicals, such as fertilizers and chemical. Demand for organic products mainly comes from countries in the western of Europe, in the northern America, in the East Asia. Besides promoting health for human and the environment, organic farming can also increase income for farmers due to the higher price of organic products compared to ordinary agricultural products. The growing market share of organic products in the world is a great opportunity for agricultural producers to shift its agriculture from conventional to organic systems. This article is written based on the PSDR-LIPI research about sustainable agriculture in Vietnam in 2013, coupled with current news on Vietnam's organic farming today. The research result shows that the opportunity to reach a large organic market has not been caught by the agricultural producer countries, such as Vietnam. Until now, organic agriculture in Vietnam has not developed rapidly, although it has spread in some provinces. The slow growth of organic agriculture is as the consequence of several things, such as the orientation of agricultural development which emphasize more on quantity and not quality, lack of legal framework, and complicated and high investment costs for developing organic farming.Keywords:organic farming, organic market, legal framework, high investment, agriculture AbstrakProduk-produk organik saat ini sangat potensial untuk dikembangkan karena semakin besarnya minat konsumen dunia akan produk makanan yang bebas dari penggunaan bahan-bahan kimia, seperti pupuk dan pestisida kimia, sehingga aman untuk dikonsumsi. Permintaan produk-produk organik terutama datang dari negara-negara Eropa Barat, Amerika Utara, serta Asia Timur. Berbagai keuntungan yang bisa didapatkan dari pertanian organik adalah peningkatan kesehatan tubuh, kesehatan ekosistem (tanah, air, hewan, dan tumbuhan), serta peningkatan penghasilan bagi para petani karena harga produk organik yang lebih tinggi dibandingkan dengan produk-produk pertanian pada umumnya. Semakin besarnya pangsa pasar produk organik di dunia merupakan kesempatan besar bagi para produsen pertanian untuk beralih dari sistem konvensional ke sistem organik. Artikel ini ditulis berdasarkan penelitian yang dilakukan oleh penulis bersama dengan tim peneliti PSDR-LIPI lainnya tentang pertanian berkelanjutan di Vietnam pada tahun 2013, dan ditambah dengan berita-berita terkini tentang pertanian organik Vietnam. Hasil penelitian dan penelusuran menunjukkan bahwa kesempatan untuk meraih pasar organik yang besar belum banyak ditangkap oleh negara-negara produsen dan pengekspor hasil pertanian, misalnya Vietnam. Hingga saat ini, pertanian organik di Vietnam belum berkembang pesat, walaupun keberadaannya telah tersebar di beberapa daerah. Lambatnya perkembangan pertanian organik ini disebabkan oleh beberapa hal, di antaranya pembangunan pertanian yang masih berorientasi pada masalah kuantitas dan bukan kualitas, belum ada tuntutan yang besar dari pasar domestik untuk masalah keamanan pangan, dan besarnya biaya investasi untuk sebuah pertanian organik.Kata kunci: pertanian organik, pasar produk organik, kerangka hukum, investasi besar, dan pertanian